A forma reduzida da expressão a(x + a)3 − a(x − a)2 + x(a − x)3 é
Soluções para a tarefa
Respondido por
5
Resposta:
Explicação passo-a-passo:
ax+a²(3) -ax +a²(2) + ax -x²(3)
3ax+3ax²-2ax+2a²+3ax-3x²
6ax-2ax+5ax²-3x²
3ax+5ax²-3x²
Respondido por
12
Resposta:
a4 − x4 − a3 + 4ax3 + 4a3x − ax2 + 2a2x.
Explicação passo-a-passo:
Tem-se:
(x + y)3 = x3 + 3x2y + 3xy2 + y3
e
(x − y)3 = x3 − 3x2y + 3xy2 − y3
Assim:
a(x + a)3 − a(x − a)2 + x(a − x)3 = a(x3 + 3ax2 + 3a2x + a3) − a(x2 − 2ax + a2) + x(a3 − 3a2x + 3ax2 − x3)
= ax3 + 3a2x2 + 3a3x + a4 − ax2 + 2a2x − a3 + a3x − 3a2x2 + 3ax3 − x4 = a4 − x4 − a3 + 4ax3 + 4a3x − ax2 + 2a2x.
Perguntas interessantes